Outpacing conventional nicotinamide hydrogenation catalysis by a strongly communicating heterodinuclear photocatalyst - Linda Zedler (Nature Communications, 2022)
Although multinuclear, supramolecular photocatalysts show promise in their ability to separate the processes required for lightdriven energy production into light absorption, charge separation and fuel production by individual parts of the molecule, mechanistic understanding of the performance limiting processes are lacking. Here the authors synthesize two new dinuclear catalysts and compare them to a benchmark through detailed spectroscopic studies, obtaining significant chemical insight.